The Obstacles For Middle School Students In Online Learning Through The Google Classroom Application - Suripah, Suripah; Junsandri, Muhammad (Prima: Jurnal Pendidikan Matematika, 2025)
Distance learning through the Google Classroom application is the main alternative for seventh grade junior high school students during the COVID-19 pandemic. However, there are many obstacles faced by students during the learning process. This study aims to identify the obstacles experienced by seventh grade junior high school students when participating in post-COVID-19 learning through the Google Classroom application. The research method used is qualitative with data collection techniques through interviews and observation. The results showed that the main obstacles experienced by students were limited internet access, lack of motivation and self-discipline, and difficulties in understanding the material being taught. In overcoming these obstacles, students need support and assistance from parents and teachers. Therefore, more intensive efforts are needed to provide adequate infrastructure and necessary training for students and parents to be able to take part in distance learning properly through the Google Classroom application.